Evaluation of efficiency the commercial influenza vaccines used in Iraq by ELISA technique. - S .Jasim, Nafea; Abid- Jabber, Shiema (Al-Qadisiyah Journal of Pure Science, 2018)
This study was done to evaluate types of inactivated influenza vaccines in poultry field in Iraq to reduce high incidence outbreaks of disease to minimize high ecomoical losses in broiler and layers . the efficacy of vaccines on immune response was evaluated depending on indirect immune sorbent assay (ELISA) test at (18,25,32,40) days of age in experiment consisting of 800 chicks . The results revealed high significant titer of immune response in the vaccinated groups comparison with control group , and results showed significant titer of immunity response in subgroups , 2, 4 comparison with other subgroups . the influenza vaccine from intervet company showed immune response more than other vaccines.